ANALISIS HARGA OBAT DAN ALAT KESEHATAN DIMASA PANDEMI COVID-19 (STUDI LITERATUR PEMIKIRAN IBNU TAIMIYAH DAN ABU YUSUF) - Zuhrotun Nisa' Sukaiyan; Lilik Rahmawati; Maulana Firdaus (Universitas Muhammadiyah Prof Dr Hamka, 2022)
The COVID-19 pandemic has had a tremendous impact on the health sector. This study aims to analyze the prices of drugs and medical devices during the COVID-19 pandemic from the perspective of Ibn Taimiyah and Abu Yusuf. The research method used in this research is literature study. The price of masks which are usually only Rp. 25,000, at the beginning of the pandemic it became Rp. 500,000, Dettol instant hand sanitizer which normally costs Rp. 12,600 to Rp. 126,000. The government's policy to minimize price increases is by limiting the export of masks and supervising traders. This policy is relevant to the thought of Abu Yusuf who said that he did not agree with the government that set the price. The thoughts of Abu Yusuf who oppose the opinion that prices are inversely proportional to the amount of inventory are not relevant to the conditions that occur. If viewed from Ibn Taimiyah's thought, there are individuals who commit price fraud while the goods are really needed by the community, the government is allowed to set prices, but the government does not do it and only makes efforts to normalize prices. Keywords; Price Mechanism, COVID-19, Abu Yusuf, Ibn Taymiyya.